The enhanced of photoresponse of ZnO nanorods film-coated by Cu2O. (June 2020) - Maryam, S; Dewi, A S P; Mufti, N; Muyasaroh, A F; Taufiq, A; Hidayat, A; Sunaryono
Abstract: Light detectors are widely used in generating energy from sunlight, medicine, space communications, ozone layer monitoring and missile warning systems, and others. The active materials that potential used as a detector of visible light and UV is ZnO. However, ZnO has a high bandgap of 3.04 eV so it is not suitable for absorbing light at short wavelengths. Cuprous oxide ( Cu2 O) is a p -type of semiconductor with a small band, therefore it can increase the wavelength absorption range. The aim of this study is to improve the light response of ZnO nanorods by coating Cu2 O. The samples were characterized by X-ray Diffractometer (XRD), Scanning Electron Microscopy (SEM), UV-Vis Spectrometry, FTIR, and photoresponse test. The results show coating Cu2 O on ZnO nanorods succeeded in reducing the bandgap value, which is 2.47 eV. Reducing the band gap value is in accordance with the photoresponse test. The response of a sample that has a small bandgap is a fast response.